STRUCTURED PHYSICAL ACTIVITY MODULE FOR CHILDREN WITH AUTISM: ENHANCING MOTOR, SOCIAL, AND BEHAVIORAL DEVELOPMENT - Othman, Syuhadah; Irin, Eshelvana Elve; Zainudin, Aisyah; Nazarudin, Mohamad Nizam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Physical fitness is a fundamental determinant of health and functional independence, particularly for individuals with special needs who often face barriers to physical activity. Aquatic environments offer unique therapeutic and educational advantages, yet structured aquatic interventions remain underexplored within Malaysian special education contexts. This study aimed to investigate the effectiveness of a structured aquatic program in enhancing muscle strength, balance, and coordination among students with special needs, and to assess the sustainability of these improvements over time. A quasi-experimental single-group pre-test–post-test design was employed involving four students (N = 4) from a Malaysian special education center. The 12-week aquatic program was based on the Halliwick Concept and Aquatic Sensory Integration Framework, with three evaluation phases: pre-test, post-test, and post-test 2 (follow-up). Performance was assessed through push and glide, floating, bubble jump, and flutter kick tests. Data were analysed descriptively and supported by observational records. Significant improvements were observed across all components, particularly in propulsion, balance, and endurance. Average gains ranged from 80% to 120%, with retention exceeding 80% during the follow-up phase. Participants also demonstrated increased confidence, motivation, and water adaptability. The structured aquatic program effectively enhanced physical fitness and sustained motor performance among students with special needs. The findings support the integration of aquatic-based interventions into Malaysia’s inclusive education framework as a pedagogical and rehabilitative strategy promoting lifelong participation and wellbeing.